Skin expression of mammalian target of rapamycin and forkhead box transcription factor O1, and serum insulin-like growth factor-1 in patients with acne vulgaris and their relationship with diet - Agamia, N.F.; Abdallah, D.M.; Sorour, O.; Mourad, B.; Younan, D.N. (British journal of dermatology (1951), 2016)
Summary Background Acne vulgaris is a multifactorial disorder of the pilosebaceous units. Several studies have reported that insulin‐like growth factor (IGF)‐1, forkhead box transcription factor (Fox)O1 and mammalian target of rapamycin (mTOR) interactions may be the key to understanding the links between genetic and environmental factors in acne vulgaris. Objectives To evaluate the immunohistochemical detection of mTOR and FoxO1 in the skin, and the serum level of IGF‐1 in patients with acne vulgaris. Methods This study was carried out on 60 participants, including 40 patients with acne and 20 controls. A diet questionnaire was administered to the patients and controls. Serum levels of IGF‐1 were measured using enzyme‐linked immunosorbent assay, and skin biopsies were taken from lesions on the backs of the patients and controls. FoxO1 and mTOR expression was detected using immunohistochemistry. Results A significantly higher serum IGF‐1 level was found in the patients with acne than in the controls. The cytoplasmic expression of FoxO1 was found to be significantly greater in the acne group, whereas in the control subjects this expression was likely to be nuclear. Both the cytoplasmic expression and the nuclear expression of mTOR were significantly more intense in the patients with acne than in the controls. Excess consumption of a high‐glycaemic‐load diet was significantly associated with higher serum levels of IGF‐1 and cytoplasmic expression of FoxO1 and mTOR. Conclusions These results suggest that FoxO1, mTOR, serum IGF‐1 and a high‐glycaemic‐load diet may play a role in acne pathogenesis. What's already known about this topic? A high‐glycaemic‐load diet and insulin‐like growth factor‐1 play roles in the induction of acne. Increased mammalian target of rapamycin (mTOR)C1 signalling has been reported in patients with acne compared with healthy controls. What does this study add? This study provides immunohistochemical evidence of increased cytoplasmic expression of the metabolic transcription factor FoxO1 and increased expression of mTOR in the skin of patients with acne. We provide experimental evidence supporting the hypothesis of decreased nuclear FoxO1 signalling in patients with acne. What is the translational message? Nutritional therapy for acne should (i) normalize total calorie intake, (ii) lower glycaemic load and (iii) restrict total dairy protein consumption. Understanding nutrient signalling may help dermatologists to understand the central role of the Western diet in the pathogenesis and treatment of acne. Our results may offer novel therapeutic strategies for the treatment of acne based on upregulation of nuclear FoxO1. Linked Comment: Melnik. Br J Dermatol 2016; 174: 1186–1188. Plain language summary available online